Assortative mating preferences among hybrids offers a route to hybrid speciation (2009)
Homoploid speciation generates species without a change in chromosome number via introgressive hybridization and has been considered rare in animals. Heliconius butterflies exhibit bright aposematic color patterns that also act as cues in assortative mating. Heliconius heurippa has a color pattern that can be recreated by introgression of the H. melpomene red band into an H. cydno genetic background. Wild H. heurippa males show assortative mating based on color pattern and we here investigate the origin of this preference by studying first?generation backcross hybrids between H. melpomene and H. cydno that resemble H. heurippa . These hybrids show assortative mating preferences, showing a strong preference for their own color pattern over that of either parental species. This is consistent with a genetic basis to wing pattern preference and implies, first, that assortative mating preferences would facilitate the initial establishment of a homozygous hybrid color pattern by increasing the likelihood that early generation hybrids mate among themselves. Second, once established such a lineage would inherit assortative mating preferences that would lead to partial reproductive isolation from parental lineages. Homoploid hybrid speciation is the establishment of a reproductively isolated lineage through hybridization without a change in chromosome number (Coyne and Orr 2004). It is therefore distinct from the numerous examples of hybrid speciation through allopolyploidization in plants (Ramsey and Schemske 2002). Although skepticism about the importance of this process in animal speciation remains, several cases of homoploid hybrid speciation have recently been reported (Mallet 2007; Mavárez and Linares 2008).